La sensibilité au contraste: une réalité clinique. I. Mesure et interprétation - Bolduc, M.; Simonet, P.; Gresset, J. (Canadian Journal of Optometry, 2026)
In this article the characteristics of tbe contrast sensitivity function will be presented along with the different techniques to measure it. Besides the techniques used in research laboratories, there are many conttast sensitivityy tests that are more suited for clinical use. Some of them should be considered as low contrast visual acuity charts. The objective of this article is to increase the awareness of clinicians about the contrast sensitivity function and about the various measurements of this funtion.